Engine Torque Control of Spark Ignition Engine using Fuzzy Gain Scheduling - Aris Triwiyatno; Mohammad Nuh; Ari Santoso; I Nyoman Sutantra (Universitas Ahmad Dahlan, 2012)
In the spark ignition engine system, driver convenience is very dependent on satisfying engine torque appropriate with the throttle position given by the driver. Unfortunately, sometimes the fulfillment of engine torque is not in line with fuel saving efforts. This requires the development of high performance and robust power train controllers. One way to potentially meet these performance requirements is to introduce a method of controlling engine torque using fuzzy gain scheduling. By using this method, the throttle opening commanded by the driver will be corrected by throttle correction signal that guarantees engine torque output will follow the desired engine torque input, and also reducing fuel consumption. In this case, spark ignition engine with automatic transmission is used to meet a good performance under this controller design.